Organismo de reestructuración agrícola - plan parcial M.A.N.G.O. del corredor Fusagasugá – Girardot (2019)
The architectural project is based on the need for agricultural recovery, providing new knowledge bases and at the same time implementing technology as a complement to agricultural tasks. Focused on producers and young people who value agriculture as the basis of the region's economy. Giving this way the theory of the extension of agriculture by means of architecture, giving place to the greater possible production in less area, with new techniques in where the knowledge is fomented and at the same time to foment the appropriation of the land. The form of the project deals with the concept of land mimicking as it is on a land with several slopes. This also helps in the warm Girardot climate in which it is located, as the inclined roofs facilitate the exit of hot air, handling wood and glass as a wrapping, in order to take advantage of the greatest possible entry of natural light and at the same time insulate the sun's rays by means of a material that is not conductive. In its main structure is developed porticos in metal structure of lights of 7.5 meters and 10.6 meters, due to the spaces required by the project where agricultural machinery plays an important role. In other spaces of the project, the wooden structure is managed, which is congruent with the agricultural sector. So the result of the project is to be able to strengthen agricultural training and technification through architectural spaces, in which knowledge is provided by all and for all.